How Can Cancer-Associated Anemia Be Moderated with Nutritional Factors and How Do Beta Vulgaris L. Ssp. Esculenta Var. Rubra Modify the Transmethylation Reaction in Erythrocytes in Cancerous Patients? - Blázovics, Anna; Nyirády, Péter; Romics, Imre; Szűcs, Miklós; Horváth, András; Szilvás, Ágnes; Székely, Edit; Szentmihályi, Klára; Bekő, Gabriella; Sárdi, Éva (IntechOpen, 2012)
None